Corrosion Resistance Measurement of 316L Stainless Steel Manufactured by Selective Laser Melting - Guzmán Nogales, Rigoberto; Estupiñan López, Francisco Humberto; Gaona Tiburcio, Citlalli; López Botello, Omar Eduardo; Ramírez Rodríguez, Juan Gabino; Zambrano Robledo, Patricia del Carmen (Molecular Diversity Preservation International, 2021)
Selective laser melting (SLM) technology is ushering in a new era of advanced industrial production of metal components. It is of great importance to understand the relationship between the surface features and electrochemical properties of manufactured parts. This work studied the influence of surface orientation on the corrosion resistance of 316L stainless-steel (SS) components manufactured with SLM. The corrosion resistance of the samples was measured using linear polarization resistance (LPR) and electromechanical noise (EN) techniques under three different environments, H2O, 3.5 wt.% NaCl, and 20% H2SO4, analyzing the horizontal (XY) and vertical (XZ) planes. The microstructure and morphology of the samples were obtained by optical (OM) and scanning electron microscopy (SEM). The obtained microstructure showed the grains growing up from the fusion line to the melt pool center and, via SEM-EDS, the presence of irregular and spherical pores was observed. The highest corrosion rate was identified in the H2SO4 solution in the XZ plane with 2.4   10